Perfil socioeconômico dos pescadores profissionais de Guaíra – Paraná - Yunes, Rosinara Virgínia Ferreira (2021)
The present study aimed to characterize the socioeconomic profile of professional fishermen from Guaira in the state of Parana. The socioeconomic characteristics were described from interviews structured through the application of questionnaires, with 48 fishermen between march and october 2020. The questions addressed themes related to age group, gender, education, housing, family income, vessel characteristics, fishing methods, fishing and fish. The fishing activity is carried out mostly by men, with an average age of 47.9 years and with low education. Fishing activity is the exclusive occupation to all respondents, with experience ranging from three to fifty years. The most reported type of housing was masonry (60%), mostly with electricity and septic tank. Monthly income ranged from 1 to 4 minimum wages (69% of respondents). The most used type of vessel was the boat without a steering wheel (96%) with a 15 HP engine. The most used equipment were the gillnet (48%) and the longline (46%). The preferred place for fishing was upstream from the Ayrton Senna Bridge. The time spent in fishing activities ranged from 4 to a maximum of 10 hours a day. It was also observed that the amount of fish ranged from 20 to 260 kg per week. The main destination for fish was the fish market/local trade/consumer (69%). Armado, curimba, curvina and pati stood out as the most captured species. Professional fishermen in Guaira depend on fishing to support their families.